2010
DOI: 10.1021/ar900272k
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Chemistry of Imidodiphosphinates from Investigations of Tellurium-Centered Systems

Abstract: CONSPECTUS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 48 publications
0
53
0
2
Order By: Relevance
“…[ [3] However, silver(I) halide complexes had previously eluded characterization owing to facile decomposition. [4] We have previously shown that the phosphorus-tellurium bond is stabilized by a negative charge in the anionic ligands {[R 2 P(Te)] 2 N} − [5] and we reported the X-ray structures of hexameric and tetrameric Ag(I) complexes of this ligand for R = iPr and Ph, respectively. [6] In a sequel to that work we have now investigated the reaction of the P-Te dianion [tBuN(Te)P(-NtBu) 2 P(Te)NtBu)] 2− (A) [7] with silver(I) iodide and found, unexpectedly, that a AgI complex of the neutral monotelluride ([tBu(H)N(Te)P(-NtBu) 2 PN(H)tBu]) (B) [8] is formed.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[ [3] However, silver(I) halide complexes had previously eluded characterization owing to facile decomposition. [4] We have previously shown that the phosphorus-tellurium bond is stabilized by a negative charge in the anionic ligands {[R 2 P(Te)] 2 N} − [5] and we reported the X-ray structures of hexameric and tetrameric Ag(I) complexes of this ligand for R = iPr and Ph, respectively. [6] In a sequel to that work we have now investigated the reaction of the P-Te dianion [tBuN(Te)P(-NtBu) 2 P(Te)NtBu)] 2− (A) [7] with silver(I) iodide and found, unexpectedly, that a AgI complex of the neutral monotelluride ([tBu(H)N(Te)P(-NtBu) 2 PN(H)tBu]) (B) [8] is formed.…”
Section: Introductionmentioning
confidence: 95%
“…Kuhn et al reported the first stable complex, M(CO) 5 (TePtBu 3 ), in 1985 and obtained the crystal structure of the chromium derivative. [2] More recently, du Mont et al were able to structurally characterize the first Ag(I) complexes of a trialkylphosphane telluride and showed that the tellurium-centered ligand may function in a bridging mode e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent synthetic approaches to GST have focused on atomic layer deposition (ALD) methods to achieve conformal coverage of the thin films on a high aspect-ratio trench pattern [6]. Binary organometallic complexes containing Ge-Te and Sb-Te bonds are useful as single source precursors (SSPs) in the metal organic chemical vapor deposition (MOCVD) of GeTe and SbTe thin films [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, considerable attention is focused on the design of molecular precursors that will produce metal tellurides of high purity in the form of thin films or quantum dots. In this connection the weakness of the P- 15,16 Other areas of current interest include the stabilization of electrophilic tellurium cations, e.g. Te 2+ and ArTe + , by phosphine donors (Section 4) 17 and weak P III ···Te interactions (Section 5.3).…”
mentioning
confidence: 99%